THEORIES OF DEMOCRATIC CONTROL OF ARMED FORCES AND THEIR APPLICATION DURING CONFLICT - Ivanec, Taras (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
This thorough examination investigates the development and obstacles of Democratic Control of Armed Forces (DCAF) within the framework of Ukraine’s persistent conflict with Russia from 2014 to 2024. The conflict, initially characterized by the annexation of Crimea and expanding into a full-scale war, highlights the imperative of combining military effectiveness with democratic responsibility, particularly in the context of hybrid warfare. Fundamental theories – Huntington’s civil-military interactions principles, Janowitz’s professionalization, Schiff’s concordance model, and Feaver’s principal-agent theory – offer essential insights for ensuring oversight during combat. These frameworks underscore the significance of civilian authority, public trust, transparency, and mutual comprehension, however encounter challenges when authoritarian inclinations or hybrid threats obscure civil-military demarcations. Ukraine’s experience illustrates that including societal engagement – via civic groups, media, diaspora activity, and technological platforms – substantially improves openness and accountability. The extensive participation of civil society, especially during periods of intensified conflict, demonstrates a transition to hybrid supervisory frameworks in which societal entities enhance formal institutions, hence bolstering democratic resilience during crises. External circumstances, particularly Russia’s annexation of Crimea and hybrid strategies, serve as drivers for changes aimed at strengthening military integrity and democratic supervision. These pressures expedite legislative and societal reforms focused on enhancing military openness, restructuring command hierarchies, and fostering public discourse. The Ukrainian situation illustrates how external dangers can act as both stressors and accelerators for the reinforcement of democratic principles, compelling institutions to adjust to emerging hybrid difficulties. The integration of institutional reforms and societal engagement demonstrates a comprehensive approach to civil-military interactions. Technological capabilities enable individuals to engage actively in the oversight of military actions, elevating accountability requirements above conventional models. Civil society initiatives, diaspora efforts, and technological platforms collaboratively enhance social cohesion and resilience, essential in both conflict situations and the maintenance of democratic legitimacy. This dynamic process underscores the importance of adaptive governance structures that can respond to evolving military threats while maintaining democratic standards. Moreover, international cooperation and comparative experiences offer valuable lessons for Ukraine, facilitating the adoption of best practices in civil-military relations. Ultimately, the Ukrainian case emphasizes that sustainable DCAF relies on a delicate balance between security imperatives and the preservation of civil liberties, especially in volatile geopolitical environments.